Oblique Right‐Lateral Faulting Along the Northern Margin of the Ili Basin in the Northern Tian Shan, Northwest China. Issue 10 (21st October 2020) - Wu, Chuanyong; Ren, Guangxue; Yu, Jingxing; Zheng, Wenjun; Li, Xinnan; Liu, Jinrui; Wang, Siyu; Li, Chuanyou; Zhang, Zhuqi; Yang, Huili; Zhang, Dongli
Abstract: The quantification of the geometry and kinematics of the boundary faults of an active orogenic belt is key to exploring its deformation pattern. The Kashihe fault (KSHF), which bounds the northern margin of the Ili Basin and is more than 400 km long, is a WNW‐striking fault in the northern Tian Shan. Although the KSHF displays active faulting and is the seismogenic fault of the 1812 M s 8 Nilka earthquake, the quantitative slip rate and its role in regional strain accommodation have not been reported. Here, we quantify the late Quaternary activity of the KSHF based on high‐resolution remote sensing image interpretations and detailed field investigations. Six field observation sites along a 270 km active fault in the Chinese Tian Shan indicate that the KSHF is characterized by dextral strike‐slip faulting and N‐S thrusting. Based on the surveying of offset geomorphic surfaces with an unmanned drone and the dating of late Quaternary sediments using optically stimulated luminescence (OSL) and radiocarbon methods, we estimated a late Quaternary right‐lateral strike‐slip rate across the fault of 2.39 ± 0.55 mm/yr and a shortening rate of 0.62 ± 0.30 mm/yr. Analysis of field investigations and fault section exposing indicated that a young paleoearthquake event occurred on the western segment of the KSHF. Active tectonics around the Ili Basin imply that the rigid Ili block extrudes westward along its boundary strike‐slip faults and rotates counterclockwise. We propose that this block rotation driven by dextral faulting accommodates regional N‐S convergence and sinistral shearing. Key Points: A dextral slip rate of 2.39 ± 0.55 mm/yr and shortening rate of 0.62 ± 0.30 mm/yr are estimated for the Kashihe fault The Ili Basin presents counterclockwise rotation and is westward extruded The counterclockwise rotation of triangular blocks driven by dextral slip faulting accommodates the regional deformation